Formative research identifying message strategies for a campus bicycle safety campaign using self-determination theory and the social norms approach. (December 2019) - Grayson, Andrew; Totzkay, Daniel S.; Walling, Brandon M.; Ingalls, Jalyn; Viken, Greg; Smith, Sandi W.; Silk, Kami J.
Highlights: A majority of student bicyclists on a college campus did not use bike lanes while cycling. SNA and SDT possess utility in bicycle safety message design. Implications for message interventions are discussed. Abstract: This formative study investigates the utility of the social norms approach (SNA) and self-determination theory (SDT) in framing safe bicycling messages with the goal of increasing intention to use bicycle lanes on a university campus. In Study 1, observational data showed that the majority of campus bicyclists did not use designated bike lanes while cycling; thus, intention to use bicycle lanes was chosen as the dependent variable for Study 2. Survey data (n = 168) collected from college students measured SNA and SDT constructs related to intention to use bicycle lanes, including descriptive norms, injunctive norms, autonomy, competence, and relatedness. Results indicate that different aspects of both the SNA and SDT are viable approaches for developing bicycle safety campaign messages, as competence, relatedness, and injunctive norms were significant predictors of intention to use bicycle lanes. Implications for the development of campaign messages are discussed, and information is presented to assist other groups so they can use the same process to develop relevant campaign messages.